1971
DOI: 10.1203/00006450-197109000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-induced Lipolysis and Its Relation to Oxygen Consumption in the Newborn Piglet

Abstract: ExtractThe relation between changes in oxygen consumption (VO 2 ) (in milliliters per kilogram and minute) and changes in levels of free fatty acids (FFA) and glycerol in plasma, lactate, pyruvate, and glucose levels in blood, and skin and rectal temperatures following norepinephrine or epinephrine infusions has been studied in neonatal piglets who lack brown fat and rapidly increase their body fat content after birth. Fourteen animals, age 17 hr-13 days (Table L4), each received two 25-min infusions of 2.0 /i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…In the present study, both breeds of pig lets responded to cold by a rise in the plasma concentration of adrenaline and noradrena line as previously reported [11,22]. The increase in the level of plasma glucose level that was observed at both 2 and 24 h of age is consistent with earlier observations [8,26]. This presumably results from the effect of catecholamines on the stimulation of liver glycogenolysis [1,32] and/or on the inhibi tion of glucose uptake by the skeletal muscle [7], The higher level of basal plasma level of FFA in Ms piglets reflects the higher content of fat in colostrum of Ms sows.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, both breeds of pig lets responded to cold by a rise in the plasma concentration of adrenaline and noradrena line as previously reported [11,22]. The increase in the level of plasma glucose level that was observed at both 2 and 24 h of age is consistent with earlier observations [8,26]. This presumably results from the effect of catecholamines on the stimulation of liver glycogenolysis [1,32] and/or on the inhibi tion of glucose uptake by the skeletal muscle [7], The higher level of basal plasma level of FFA in Ms piglets reflects the higher content of fat in colostrum of Ms sows.…”
Section: Discussionsupporting
confidence: 82%
“…This supports, in part, the observations of Curtis and Rogler and Persson et al that intravenous injections (14) or infusions (12) of norepinephrine induce little or no increases in pIasma NEFA of 6 to 30-hr-old swine. Norepinephrine induced appreciable lipolysis in older animals (> 54 hr) in those studies.…”
supporting
confidence: 89%
“…Persson et at?. (12) demonstrated that norepinephrine infusions induced less increase in blood glucose in young (1-2 days old) than in older (5-12 days old) piglets.…”
mentioning
confidence: 97%
“…In fact, a low total plasma-protein-binding capacity for T4 with a concomitant high free T4 level occurs in pigs less than 12 h o f age {Slebodzihski, 1965a) and may thus enable a quicker metabolic action of the hormones. The newborn pig has no ana tomically detectable brown adipose tissue {Leblanc and Mount, 1968;Rowlatt et aL, 1971) and is different from the newborn o f some other species as it does not react metabolically to noradrenaline {LeBlanc and Mount, 1968;Persson et al, 1971;Kaciuba-Uscilko and Poczopko, 1973). On the basis o f these findings it has already been postulated that in the pig T4 is the major hormonal factor responsible for the metabolic adaptation to extrauterine life.…”
Section: Discussionmentioning
confidence: 87%